DWITUNGGAL DALAM DIMENSI LONTAR: DUALISME DALAM PENCIPTAAN SENI LUKIS - Yudha, I Made Bendi (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Art is an expression of feeling representing the crystalization of ideas that result from imaginative experiences through observation and exploration of such social life as religion, culture, custom and tradition, and natural environment. These are all encouraged by internal stimulus and intuitive urge that stimulate emotion and imagination to be expressed in a painting art. To Balinese people, lontar is one of the human cultural achievements containing dual values and spiritual teaching to guide people to have a physically and mentally harmonious and balanced social life. The observed and comprehended values contained in lontar have inspired the writer during the creative process. By understanding the balance concept of contained in lontar we can wisely interpret the phenomena of life in our recent social environment which is characterized by intrigues of personal interests and violation of moral norms that result in horizontal conflicts as represented by the changes of life style and mental attitude such as damaged environment, degraded human value and status, pressure to others, and so on. The understanding of the values has inspired to visualize the phylosophical and conceptual context in the painting artwork of abstractive and representative form with variative colors by impasto technique to have artistic personal symbols. Keywords: painting, dual dimension of life